Response of Papaya (Carica Papaya L.) to Major Mineral Nutrients - Bindu B (Department of Pomology and Floriculture, College of Agriculture, 2003)
An experiment was conducted in the Department of Pomology and Floriculture, College of Agriculture, Vellayani during 2001-2002, to study the response of major plant nutrients viz., nitrogen, phosphorus and potassium on growth, yield and quality of papaya under Kerala conditions and to standardise the optimum dose of these nutrients. The experiment was conducted in 33 confounded factorial RBD, confounding NPK in replication 1 and Np2K2 in replication 2. The present study revealed that application of nitrogen, phosphorus and potassium increased plant height, girth and number of leaves. The highest plant height was obtained with the combined application of 200 g N, 300 g P and 500 g K plan' year-', while the highest plant girth was obtained with application of 250 g N, 300 g P and 500 g K. Combined application of 300 g N, 250 g P and 500 g K p lant' year-' resulted in the maximum number of leaves. Plants receiving a dose of nitrogen at 250 g, 300 g phosphorus and 500 g potassium plant" took the shortest time for flowering. Combined application of nitrogen at 250 g plant.", phosphorus at 250 g plant" and potassium at 500 g planr' considerably shortened the time for harvesting the first fruit. Fruit weight, number of fruits plant", yield planr' and papain yield increased by application of nitrogen, phosphorus and potassium. Application of 250 g N, 250 g P and 500 g K planr' year-' gave highest yield. Maximum fruit girth was obtained from 200 g N, 200 g P and 500 g K, whereas maximum fruit volume and pulp percentage was obtained from 250 g N, 250 g P and 500 g K. Levels of nitrogen and phosphorus tried had no significant influence on TSS and ascorbic acid content of fruits. Nitrogen at 200 g, phosphorus at 250 g planr' produced. fruits of low acidity, while potassium had no